Content of rare earth elements in soils of the Czech Republic - Benes,S. (Journal of the Czech Geological Society, 1994)
The highest contents of light lanthanides were found in soils on intermediate and igneous rocks, on deluvium soils on intermediate and acidic igneous rocks, on deluvium soils from Proterozoic shales, in paragneisses, ortogneisses and loesses loams. In contrary, the lowest representation of light and heawy lanthanides was found in soils an sands on Permian sandstones and conglomerates.The highest contents of heavy lanthanides were equal as in the light lanthanides, found in soils on acidic igneous rocks. Relatively high contents were even in soils on paragneisses, orthogneisses, granulites, mica schists and deluvium soils formed on Proterozoic shales. Soils on sands, Permian sandstones and on basic and intermediate igneous rocks showed the lowest contents.Accumulation of the most of light and heavy lanthanides in top soils, expressed in % of their content in C soil horizons, was found in top soils of sedimentary rocks. The increasing content in top soils on fluvial sediments was somewhere between 120-160 % of C horizons content. The exceptionis shown in the top soils of fluvialsediments, where the lanthanides contents were lower in comparison with C soil horizons. The top soils on igneous rocks were similar. The contents of light lanthanides were lower in top soils (50-90 %) compared with C horizon contents.Accumulation of heavy lanthanides was not well balanced in soils on igneous rocks and was between 80-120 % of C horizon content. Contents of heavy lanthanides (Tb, Lu, Yb) were lower in top soil on metamorphic rocks in all cases, in comparison with C horizons (50-90 % of their content). The content of light lanthanides was not well balanced in top soils and was between 80-120 % of the C horizon content.If we compare the contents of light and heavy lanthanides in top soils in the Czech Republic with the darks lanthanide value according to Taylor (1985 - clark concentration), then the contents of all lanthanides in top soils are between 120-160 % of the clark value.The thalium content in average sample of top soils is twice as high as the clark value.